2020
DOI: 10.3390/agronomy10071023
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Edible Coatings in Alleviating Shrivel and Maintaining Quality of Japanese Plum (Prunus salicina Lindl.) during Export and Shelf Life Conditions

Abstract: The effect of six edible coatings were investigated on the ability to alleviate shrivel and extend shelf life of plums. Fruit were subjected to a simulated shipping period (−0.5 ± 2 °C and 90 ± 5% relative humidity (RH)) for five weeks and a subsequent shelf life period (20 ± 2 °C and 80 ± 5% RH) for 20 d. Overall, the study showed that it is possible to alleviate shrivel and also extend shelf life of plum (‘African Delight™’) at export and shelf life conditions. Amongst the edible coatings investigated, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 40 publications
6
23
1
Order By: Relevance
“…These findings corroborate with Chen et al [ 92 ], who found that application of coatings delayed the rise in R CO2 of ‘Nanfeng’ mandarin during 100-day storage period at 6 °C. Moreover, the application of coatings has been shown to lower R CO2 during the storage of fruit types such as tomato [ 25 ], sweet cherry [ 93 ], plum [ 94 ], banana [ 85 ] and others. The effect of adding LM or PP to GA coatings on RCO 2 pattern was not clear; however, previous studies suggested that LM applications resulted in minor oxygen consumption and CO 2 production due to reduced microbial growth caused by active compounds in the essential oil [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings corroborate with Chen et al [ 92 ], who found that application of coatings delayed the rise in R CO2 of ‘Nanfeng’ mandarin during 100-day storage period at 6 °C. Moreover, the application of coatings has been shown to lower R CO2 during the storage of fruit types such as tomato [ 25 ], sweet cherry [ 93 ], plum [ 94 ], banana [ 85 ] and others. The effect of adding LM or PP to GA coatings on RCO 2 pattern was not clear; however, previous studies suggested that LM applications resulted in minor oxygen consumption and CO 2 production due to reduced microbial growth caused by active compounds in the essential oil [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Internal packaging refers to additional packaging materials applied around the fruit within the external package. Surface coating and waxing has been applied on apples, oranges, plums, and pomegranate to minimise moisture loss [ 8 , 11 , 12 , 13 , 14 , 15 ]. For pomegranates, heat shrinkable wraps on individual fruit in cartons have also been applied [ 8 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results suggest that the concentration of both MS and GA significantly influenced reduced weight loss when applied as surface coatings on "Wonderful" pomegranate fruit. Several studies have shown that GA and MS-based coatings inhibit migration of moisture from the fruit surface into the environment, thus reducing weight loss [23,[58][59][60].…”
Section: Weight Lossmentioning
confidence: 99%